Analisis Insektisida Organoklorin Pada Bulu Walet Sarang Putih (Collocalia fuciphaga Thunberg) - Laudensius, Oktaf; Yuda, Pramana; Atmodjo, Kianto (Universitas Atma Jaya Yogyakarta, 2003)
The objectives of this study are to find out the kind and quantitative of organochlorine insecticide in swallow (Collocalia fuciphaga Thunderberg) feathers. The samples were plumae of wing and tail feathers from the birds were catched in Siluk, Gunungkidul and Sedayu, Bantul on August and September 2002 The organochlorine insecticide compound were analysed by gas chromatography-electronic catcher detector. The analysis result found out the organochlorine insecticide in swallow feathers, were heptachlor (0-5855 ppm) and pp-DDD (0-0929 ppm).